Analisis Tindak Tutur pada Wawancara Putra Nababan dan Presiden Portugal (Kajian Pragmatik) - Akbar, Syahrizal (Universitas Hamzanwadi, 2018)
This mini research aims to describe the form of speech acts in the locution, ilocution, and perlocution that exist in interviews RCTI journalist, Putra Nababan with the President of Purtugal, Antonio Covaco Silva.The research method in this research is descriptive qualitaive method. Sources of data from interviews RCTI journalist, Putra Nababan with President of Portugal, Antonio Covaco Silva. In categorizing the data, the researcher uses the techniques of referring, recording, and noting. Based on data analysis, it was concluded that interview between RCTI journalist, Putra Nababan and President of Portugal, Antonio Covaco Silva has an act of ilocution with assertive, directive, commisive, expressive, and declaration type.Keywords: locution, ilocution, perlocution, pragmatic study